2003
DOI: 10.1152/ajpheart.00359.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory stress increases receptor for lysophosphatidylcholine in human microvascular endothelial cells

Abstract: The atherogenic serum lysophosphatidylcholine (LPC) is known to mediate vascular endothelial responses ranging from upregulation of adhesion molecules and growth factors to secretion of chemokines and superoxide anion. We investigated whether endothelial cells express receptors for LPC, which may account for their actions. Human brain microvascular (HBMEC) and dermal microvascular endothelial cells (HMEC) were prepared for RT-PCR analysis for possible expression of the G protein-coupled receptors, GPR4 and G2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 26 publications
8
49
1
Order By: Relevance
“…A recent study also reported GPR4 expression in endothelial cells and further suggested that GPR4 expression is transcriptionally induced by inflammatory stress in human vascular endothelial cells (24). However, this study did not detect G2A expression, which contradicts our observations.…”
Section: G2a Is Expressed In Cell Types With Key Roles In Atherosclercontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study also reported GPR4 expression in endothelial cells and further suggested that GPR4 expression is transcriptionally induced by inflammatory stress in human vascular endothelial cells (24). However, this study did not detect G2A expression, which contradicts our observations.…”
Section: G2a Is Expressed In Cell Types With Key Roles In Atherosclercontrasting
confidence: 99%
“…Although this may reflect the use of human versus murine cells, it is also possible that differences in their preparation, or immortalization in the case of cell lines, may influence endothelial cell receptor expression, as G2A is subject to transcriptional regulation by multiple stress stimuli (25). Furthermore, it is possible that endothelial cells from different vascular sites exhibit varying patterns of receptor expression (24). Nevertheless, our data show that G2A but not GPR4 is expressed in inflammatory cells, whereas GPR4 is the predominant receptor in aortic endothelial cells that also express lower levels of G2A.…”
Section: G2a Is Expressed In Cell Types With Key Roles In Atherosclermentioning
confidence: 99%
“…PI-88 was kindly provided by Progen Pharmaceuticals (Toowong, QLD, Australia). Human brain microvascular endothelial cells (HBMEC) and human dermal microendothelial cells (HDMEC) were used in our previous study [21]. HBMEC were grown in RPMI 1640 containing 10% FBS, MEM vitamins, non-essential amino acid, sodium pyruvate (Invitrogen, Carlsbad, CA, USA), penicillin (100 U/ml), streptomycin (100 Îźg/ml) and 2 mmol/l L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…34 While a recent report argues against SPC and LPC as ligands for GPR4, 35 another line of evidence from competition binding assays shows that LPC binds to microvascular endothelial cells where GPR4 but not G2A is expressed. 36 Given the distinct expression patterns of G2A and GPR4, one may speculate that these 2 receptors are responsible for LPC-induced chemotaxis differentially in various cell contexts. In this respect, it is interesting to note that although expression of GPR4 is lower than G2A in mouse primary and J774A.1 macrophages by RT-PCR (L.V.Y.…”
Section: Org Frommentioning
confidence: 99%